2013
DOI: 10.1093/cvr/cvt178
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of progranulin exacerbates atherosclerosis in ApoE knockout mice

Abstract: PGRN seems to be involved in the pathogenesis of atherosclerosis, possibly by various anti-atherogenic effects, including modulation of local and/or systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 28 publications
1
67
0
Order By: Relevance
“…Indeed, others have reported that deletion of progranulin increases macrophage CD36 expression and induces local inflammation. 73 Several studies have linked progranulin activity with IL-6 expression; 74, 75 however, we are unaware of previous work linking progranulin deficiency and increased expression of CD126, a receptor of IL-6. As expected from previous work, wt microglia MHC class II expression was increased following BMT, 48 and this effect was equivalent in wt and Grn −/− BMT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, others have reported that deletion of progranulin increases macrophage CD36 expression and induces local inflammation. 73 Several studies have linked progranulin activity with IL-6 expression; 74, 75 however, we are unaware of previous work linking progranulin deficiency and increased expression of CD126, a receptor of IL-6. As expected from previous work, wt microglia MHC class II expression was increased following BMT, 48 and this effect was equivalent in wt and Grn −/− BMT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…PGRN plays a critical role in various physiological processes, including early embryogenesis, wound healing, and host defense responses. PGRN is also widely involved in the pathogenesis of many diseases, including autoimmune disorders, atherosclerosis, and cancer [19][20][21]. Recent studies have highlighted the important role of PGRN in inflammatory responses and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…PGRN-mediated inhibition of TNFα activity has been well established [11; 12; 13; 14; 15; 16; 17; 18; 19]. For instance, PGRN diminishes TNFα-trigged production of reactive oxygen species in neutrophils [11].…”
Section: Introductionmentioning
confidence: 99%